Determinants of Stunting among Children Aged 0-59 Months in Gunungpati District, Semarang City - Syarifah Kamalia Putri Ardhana; Lukman Fauzi (Universitas Negeri Semarang, 2025)
Background: Stunting, a consequence of chronic malnutrition, is a growth disorder causing children to be too short for their age. This study aimed to identify family and environmental variables that determine stunting in children aged 0–59 months in Gunungpati District, Semarang City, in 2022. Methods: This observational analytic study using a case-control design with 45 cases and 45 controls, selected by simple random sampling. Independent variables assessed were maternal age, birth spacing, number of children in the family, drinking water source, and latrine condition, all derived from secondary data. Data were analyzed using univariate, bivariate (chi-square), and multivariate (logistic regression) methods. Results: Bivariate analysis yielded significant associations for maternal age (p= 0.002) and number of children in the family (p= 0.003). Birth spacing (p= 0.168), drinking water source (p= 1.000), and latrine conditions (p= 0.806) were not statistically significant. Multivariate analysis indicated that the two most significant determinants of stunting incidence were maternal age OR= 4.429 (95% CI: 1.829–10.726) and number of children in the family OR= 4.000 (95% CI: 1.665–9.610). Conclusion: Maternal age and number of children in the family are proven determinants associated with stunting incidence, with maternal age being the most influential determinant.